1998
DOI: 10.1093/jn/128.8.1320
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A Supplementation but Not Deworming Improves Growth of Malnourished Preschool Children in Eastern Zaire

Abstract: A randomized controlled trial was conducted in eastern Zaire to assess the effects of high dose vitamin A supplementation and regular deparasitation on the growth of 358 moderately malnourished preschool children, discharged from the hospital. The treatment groups received either vitamin A (60 mg of oily solution of retinyl palmitate, 30 mg if aged õ12 mo) every 6 mo or mebendazole (500 mg) every 3 mo; the control group received no supplementation. Anthropometric data were gathered at baseline and after 6 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 22 publications
1
51
2
Order By: Relevance
“…30 Donnen et al found that although vitamin A supplementation improved the growth of malnourished pre-school children, de-worming had no impact. 41 Our study results re ect this mixed picture. While previous studies have shown improvement in school achievement and cognitive tests following de-worming programmes, 3,39 de-worming 7-12-year-old rural Guatemalan children with high parasite loads failed to affect their school performance.…”
Section: Discussionmentioning
confidence: 51%
“…30 Donnen et al found that although vitamin A supplementation improved the growth of malnourished pre-school children, de-worming had no impact. 41 Our study results re ect this mixed picture. While previous studies have shown improvement in school achievement and cognitive tests following de-worming programmes, 3,39 de-worming 7-12-year-old rural Guatemalan children with high parasite loads failed to affect their school performance.…”
Section: Discussionmentioning
confidence: 51%
“…Only one trial included children with SAM exclusively [19]. The remaining 14 included non-malnourished and malnourished children [20-33]. VA dosing also varied; only five trials administered the recommended high-dose on day 1 [19,26,30,31,33], while the remaining administered VA doses in varying quantities and forms.…”
Section: Resultsmentioning
confidence: 99%
“…An additional four multiple dose trials recorded data after their first treatment dose, and these data were included in the single dose analysis 19 22 40 45. A subsequent sensitivity analysis that excluded data from these four multiple dose trials did not show any change in effect trends.…”
Section: Resultsmentioning
confidence: 99%